PENGOLAHAN LIMBAH CAIR LABORATORIUM KIMIA DENGAN MENGGUNAKAN METODE ELEKTROKOAGULASI DAN KOAGULAN BIJI KELOR - Syamsur, Nadia Nurafiah; Ihsan, Ihsan; Sahara, Sahara (JFT: Jurnal Fisika dan Terapannya, 2018)
This research aims to determine the characteristics of chemical laboratory wastewater which includes COD, pH, turbidity and heavy metals (Pb, Hg, and Cd) before processing and after processing using the electrocoagulation method and moringa seed coagulant. The electrocoagulation process is carried out using a pair of electrode plates made of iron as anode and cathode with a voltage variation of 6, 9 and 12 V with each coagulation process carried out for 30, 60 and 120 minutes for each voltage variation and the coagulation-flocculation method using 2.5 grams of moringa seed powder each as a coagulant with fast stirring for 5 minutes and slow stirring for 2 minutes. The results obtained from the electrocoagulation method and the coagulant method of moringa seeds, namely with pH parameters of 5, COD of 20000 ppm, turbidity of 4.09 FTU, Hg levels of 1.2857 mg / l, Pb levels of 0.090659341 mg / l and Cd levels of 0.090659341 mg / l. This shows that the electrocoagulation method and the coagulant method of Moringa seeds can reduce each of the parameters tested, both pH, COD, turbidity and heavy metals (Pb, Hg and Cd).